2003
DOI: 10.1002/cncr.11761
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of occult axillary micrometastasis in ductal carcinoma in situ

Abstract: Electrospray ionization (ESI) of tetrameric platinum(II) acetate, [Pt4(CH3COO)8], in methanol generates the formal platinum(III) dimeric cation [Pt2(CH3COO)3(CH2COO)(MeOH)2]+, which, upon harsher ionization conditions, sequentially loses the two methanol ligands, CO2, and CH2COO to form the platinum(II) dimer [Pt2(CH3COO)2(CH3)]+. Next, intramolecular sequential double hydrogen‐atom transfer from the methyl group concomitant with the elimination of two acetic acid molecules produces Pt2CH+ from which, upon eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
2
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 20 publications
4
47
2
5
Order By: Relevance
“…In another study of 102 patients with DCIS and negative axillary nodes, MM were identified in 13% on retrospective analysis. After 10-28 years of follow-up, the overall disease recurrence rate was 12% although none of these patients had been found to harbour MM and the recurrence site was not found to be the axilla in any case [67]. The low rate of local recurrence and excellent overall survival in these patients has been suggested to provide further circumstantial evidence against the significance of MM.…”
Section: Evidence Againstmentioning
confidence: 87%
“…In another study of 102 patients with DCIS and negative axillary nodes, MM were identified in 13% on retrospective analysis. After 10-28 years of follow-up, the overall disease recurrence rate was 12% although none of these patients had been found to harbour MM and the recurrence site was not found to be the axilla in any case [67]. The low rate of local recurrence and excellent overall survival in these patients has been suggested to provide further circumstantial evidence against the significance of MM.…”
Section: Evidence Againstmentioning
confidence: 87%
“…Another aspect of the argument against performing SLN biopsy in patients with a presumed diagnosis of DCIS is the problem of a positive SLN in this setting. The management of such patients is controversial as metastatic involvement of the SLN is frequently in the form of micrometastases (defined as small metastases no larger than 2 mm but larger than 0·2 mm) detected using immunohistochemistry alone 21,29,30,57 . The prognostic significance and clinical consequences of micrometastases in the SLN even in invasive breast cancer remain matters of debate.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and clinical significance of nodal meta stasis in DCIS has been evaluated in both the pre-and the post-screening era. In the pre-screening era, ALND was not performed in DCIS because of the low incidence of axillary metastasis (1%-2%), and the high morbidity associated with ALND [12,13] . This low rate of axillary lymph node involvement in pure DCIS was attributed to missed diagnosis of invasion in the final pathology of the breast specimen [2,12] .…”
Section: Discussionmentioning
confidence: 99%